Effective permeability in fractured reservoirs: discrete fracture network simulations and percolation-based effective-medium approximation - Agbaje, Tolulope (Kansas State University, 2023)
Fractured reservoirs are complex and multi-scale systems composed of matrix and fractures. Accordingly, modeling flow in such formations has been a great challenge. ... See PDF file for full abstract.
Keywords: Effective permeability; Fractured reservoir; Percolation theory; Effective-medium approximation; Discrete fracture network; Numerical simulation